KAPASITAS KEPALA DESA DALAM MEMBINA KETENTRAMAN DAN KETERTIBAN DI DESA PINTU GOBANG KARI KECAMATAN KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI TAHUN 2017-2018 - Jundra Yani; Adlin ' (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The Village Head is one of the people who exercises the rights, powers and obligations of the leadership of the Village Administration. in administering village government is the main organizer and person in charge in the field of government, development and society in the context of administering village government, general government affairs and including the development of security and order in accordance with applicable laws and regulations. The type of research used by the authors in this study is descriptive. Data collection techniques are interviews, literature studies and documentation. The data analysis technique in this study was carried out qualitatively. The results of the study explained that the capacity of the Pintu Gobang Kari village head was assessed from 3 indicators, namely basic abilities which showed that the basic ability of the Pintu Gobang Kari village head was to understand and understand security and order issues in Pintu Gobang Kari Village. According to the research informant, the village head also understands his authority in maintaining peace and security in the village. Both capacity assessments based on management capabilities show that in terms of management capabilities it is assessed that the village head has good management capabilities which can be seen from the coordination carried out by the village head when there is a security disturbance in Pintu Gobang Kari Village. Third, the capacity of the Pintu Gobang Kari village head in terms of his technical skills is still inadequate because there are no village regulations made in an effort to maintain peace and order in the village. The program that was just created was limited to the provision of security posts where the provision of security posts could only overcome the problem of theft through night patrols that were carried out, but had not been able to overcome the problem of fighting between groups or gangs in the village and also the problem of gambling. Keywords: Basic Capabilities Of The Village Head, Management Capabilities Of The Village Head, Technical Capabilities Of The Village Head